Draft Annual Plan 1994-95 Part-I Volume-I National Capital Territory of Delhi - Planning Commission (Planning Commission, 1994)
Out of the total area of 1483 Sq. Kms., 783 Sq. Kms is rural and 700 Sq. Kms. is urban. According to the 1991 Census, urban area accounted for 90% population whereas 10% population lived in rural areas. the distinction between rural and urban areas in Delhi is gradually diminishing due to its fast urbanisation. The entire rural area of Delhi is being looked after by the Delhi Municipal Corporation. For administrative convenience and development purposes, the rural area has been divided into five Development Blocks viz. Alipur, Kanjhawala (Nangloi), Najafgarh, Mehrauli and Shahdara.
Planning Department, Govt. of National Capital Territory of Delhi